2024
DOI: 10.1038/s41586-023-06956-y
|View full text |Cite
|
Sign up to set email alerts
|

Motion of VAPB molecules reveals ER–mitochondria contact site subdomains

Christopher J. Obara,
Jonathon Nixon-Abell,
Andrew S. Moore
et al.

Abstract: To coordinate cellular physiology, eukaryotic cells rely on the rapid exchange of molecules at specialized organelle–organelle contact sites1,2. Endoplasmic reticulum–mitochondrial contact sites (ERMCSs) are particularly vital communication hubs, playing key roles in the exchange of signalling molecules, lipids and metabolites3,4. ERMCSs are maintained by interactions between complementary tethering molecules on the surface of each organelle5,6. However, due to the extreme sensitivity of these membrane interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
(130 reference statements)
1
3
0
Order By: Relevance
“…The results from both IPA and DAVID implicated mitochondrial binding partners as the disrupted interaction in VAPB P56S expressing iPSC-derived MNs corroborates previously published data showing that VAPB is a critical component in tethering the mitochondria to the ER, through an interaction with PTPIP51, an interaction known to be disrupted by the VAPB P56S mutation and results in decreased MERC. 9,10,16 We confirmed the co-immunoprecipitation and mass spectrometry results through Western Blot, showing that PTPIP51 was enriched in the immunoprecipitation as well as showed decreased binding to VAPB in the VAPB P56S iPSC-derived motor neurons ( Figure 2e and Extended Data Figure 3a).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The results from both IPA and DAVID implicated mitochondrial binding partners as the disrupted interaction in VAPB P56S expressing iPSC-derived MNs corroborates previously published data showing that VAPB is a critical component in tethering the mitochondria to the ER, through an interaction with PTPIP51, an interaction known to be disrupted by the VAPB P56S mutation and results in decreased MERC. 9,10,16 We confirmed the co-immunoprecipitation and mass spectrometry results through Western Blot, showing that PTPIP51 was enriched in the immunoprecipitation as well as showed decreased binding to VAPB in the VAPB P56S iPSC-derived motor neurons ( Figure 2e and Extended Data Figure 3a).…”
Section: Resultssupporting
confidence: 70%
“…We found that the VAPB P56S iPSC-derived motor neurons exhibited a significant decrease in the percentage of mitochondrial contact with the ER on both day 35 (Figure 3a) and day 60 (Figure 3b) of differentiation, corroborating previous reports (Extended Data Figure 4a-c). 9,10,18 With this loss of MERC confirmed in our model, we next wanted to assess the functional consequence on the mitochondria. To investigate this, we used the JC-1 assay to measure the mitochondrial membrane potential (MMP).…”
Section: The Vapb P56s Mutation Leads To a Reduction In Er-mitochondr...mentioning
confidence: 79%
See 1 more Smart Citation
“…The integral ER protein, vesicle-associated membrane protein B (VAPB) forms a well-established tethering complex with the protein tyrosine phosphatase-interacting protein-51 (PTPIP51) located in the OMM [ 178 ]. Subdomains within VAPB have been shown to facilitate ER membrane curvature [ 179 ]. The dissociation of VAPB is triggered by p97/Valosin-containing protein (VCP) via the negative regulation of VPS13D, a homolog of VPS13C (PARK23), associated with early-onset autosomal-recessive PD [ 180 , 181 ].…”
Section: Regulating Er–mitochondrial Appositionmentioning
confidence: 99%
“…These sub-cellular compartments are dynamic and interact via proteins that mediate membrane anchoring and/or the exchange of molecules and ions between organelles 6 9 . Perturbation of these organelle contact sites disrupts cell and whole-body metabolism and have been linked to the patho-physiology of metabolic and neurodegenerative diseases 8 , 10 13 . Therefore, there is a need to study and understand the principles that guide the spatial organization pattern of cells and organelles in situ and their correlation to changes in animal and cell metabolism.…”
Section: Introductionmentioning
confidence: 99%